EVALUASI UJI EFEKTIVITAS EKSTRAK KAYU MANIS (Cinnamomum burmanni) SEBAGAI LARVASIDA TERHADAP KEMATIAN JENTIK NYAMUK (Aedes aegypti) - Ike Widiya R (Jurnal Kajian Kesehatan Masyarakat, 2023)
Alternative larvicides against Aedes aegypti larvae and safe for the environment, one of which is cinnamon oil which has been shown to have a larvicidal effect on larvae. Cinnamon contains flavonoid compounds which are strongly suspected to have a larvicidal effect. It can be said that this research is to determine the effectiveness of extracts from cinnamon as a larvicide against the death of Aedes aegypti mosquito larvae. And for the extraction method used in this study using the maceration method. For a concentration of 2% it can kill a total of 32 (53%) larvae, and for a concentration of 4% it can kill 43 (72%) total lava, and a concentration of 6% can kill 53 (88%) larvae, and for a positive control, namely abate (temephos). ) has the best larvicidal effect with an average % larval mortality of 100% within 1 hour. Cinnamon extract test treatments with a concentration of 2% (2ml/100ml) experienced larval death 32 (43%), and for a concentration of 4% (4ml/100ml) experienced larvae mortality 43 (53%). and for a concentration of 6%, 53 (88%) larvae died. And for temephos, it was able to kill a total of all larvae, while for negative control it did not die. The most effective concentration of cinnamon extract in killing larvae was 6%, the higher the concentration, the higher the larval mortality value.